2015
DOI: 10.3109/02699052.2015.1075155
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial attention after traumatic brain injury: The role of hemispheric specialization

Abstract: TBI may have an enduring effect on the orienting system at both neural and behavioural levels. Assessment of attention in chronic TBI can be improved by the integration of hemispheric findings that suggest disproportionate vulnerability in leftward orienting. Results may enhance clinical sensitivity to detection of subtle signs of neglect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The flow diagram in Figure 1 describes the study search and selection process and outcomes (Moher et al, 2009 ). Out of 50 abstracts screened, 18 studies met the inclusion criteria for qualitative analysis (Macflynn et al, 1984 ; Cremona-Meteyard et al, 1992 ; Cremona-Meteyard and Geffen, 1994b ; Geldmacher and Hills, 1997 ; Hills and Geldmacher, 1998 ; Bate et al, 2001 ; Van Donkelaar et al, 2005 ; Halterman et al, 2006 ; Pavlovskaya et al, 2007 ; Catena et al, 2009 ; Kim et al, 2009 ; Sinnett et al, 2011 ; Rodríguez-Bailón et al, 2012 ; Hill-Jarrett et al, 2015 ; Schmitter-Edgecombe and Robertson, 2015 ; Robertson and Schmitter-Edgecombe, 2017 ; Shah et al, 2017 ; Hromas et al, 2020 ). After thorough review of the full texts, 16 of these 18 studies met the criteria for quantitative analysis, producing 80 calculated effect size estimates for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The flow diagram in Figure 1 describes the study search and selection process and outcomes (Moher et al, 2009 ). Out of 50 abstracts screened, 18 studies met the inclusion criteria for qualitative analysis (Macflynn et al, 1984 ; Cremona-Meteyard et al, 1992 ; Cremona-Meteyard and Geffen, 1994b ; Geldmacher and Hills, 1997 ; Hills and Geldmacher, 1998 ; Bate et al, 2001 ; Van Donkelaar et al, 2005 ; Halterman et al, 2006 ; Pavlovskaya et al, 2007 ; Catena et al, 2009 ; Kim et al, 2009 ; Sinnett et al, 2011 ; Rodríguez-Bailón et al, 2012 ; Hill-Jarrett et al, 2015 ; Schmitter-Edgecombe and Robertson, 2015 ; Robertson and Schmitter-Edgecombe, 2017 ; Shah et al, 2017 ; Hromas et al, 2020 ). After thorough review of the full texts, 16 of these 18 studies met the criteria for quantitative analysis, producing 80 calculated effect size estimates for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that, in stroke, N1 is a neurophysiological index of impairment on left stimulus processing and, thus, a sign of inter-hemispheric imbalance in LHSN (15,18,19). Furthermore, a recent study comparing TBI patients with LHSN against controls showed the presence of hemispheric differences in latencies and amplitudes of the N1 component of VEPs to stimuli presented on both sides (15). These data suggest that the right hemispheric stroke imbalance model could also be applied to explain LHSN symptoms in TBI.…”
Section: Introductionmentioning
confidence: 85%
“…The neural correlates of the inter-hemispheric imbalance associated with LHSN symptoms are often assessed using visual evoked potentials (VEPs). In particular, N1 is a posterior negative deflection in the VEPs, peaking around 180 ms after stimulus presentation, with greater amplitude for stimuli presented in the contralateral hemifield (15). In stroke, it has been demonstrated that LHSN is associated with a smaller amplitude and delayed latency of N1 for left presented stimuli compared to right presented stimuli (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations